Impact of physical training on self confidence - Abd Manaf, Norsyahrina; Abu Samah, Bahaman; Ahmad, Nobaya; Othman, Jamilah; D’Silva, Jeffrey Lawrence (Science Publications, 2013)
As well as having a positive impact on our health, physical activity is useful for increasing self-confidence. In Malaysia, many physical programs have been organized, including the physical activities module included in Program Latihan Khidmat Negara (PLKN; the national services program). Unlike other modules, the physical activities module in PLKN is quite different due to the longer period it takes to accomplish the module. The main objective of the physical module in PLKN is to enhance the trainees' self-confidence and this study aims to discover the effectiveness of the module in this regard; i.e., how much self-confidence do trainees gain and is there any difference in their self-confidence before and after joining the module? This is a quantitative study in which a total of 362 trainees from Putra-Putri Training Camp at Alor Gajah, Malacca were selected as respondents based on multi-stage sampling. The analysis shows that the majority of trainees had a moderate level of self-confidence both pre- and post-test. However, the results demonstrate that the physical module did enhance the trainees' self-confidence based on the significant difference identified in the mean score between the pre- and post-test. It is recommended that PLKN in Malaysia should be implemented over a longer period; this would provide opportunities for new and challenging activities to be added to the program.